Facilitating Employee Adaptation During M&A: Lessons from Nepalese Banking Sector - Kandel, Madan (DEPAN, 2023)
This study explores the impact of mergers and acquisitions (M&A) on employee performance in Nepalese commercial banks, focusing on cultural changes, job stress, and job security. The research aims to fill a gap in the literature by addressing how these significant organizational changes influence employees in emerging markets. Using a mixed-methods approach, both quantitative and qualitative data were gathered and analyzed from 378 employees across three major banks—Nabil Bank, Nepal Investment Bank, and Himalayan Bank. Surveys and structured interviews were employed to capture a comprehensive understanding of employees’ experiences and performance levels post-M&A. The results indicate that cultural integration plays a pivotal role in influencing job satisfaction and overall performance. Employees who successfully adapted to new cultural environments demonstrated higher levels of job performance, whereas those who struggled with integration reported lower satisfaction and reduced performance. Additionally, job stress levels were found to rise significantly after M&A, which negatively impacted employee productivity. Interestingly, despite the stress, job security concerns were linked with improved performance, suggesting that employees may exert extra effort to secure their positions during uncertain times. The study underscores the importance of managing cultural transitions effectively, reducing job stress, and ensuring job security to sustain employee performance during M&A processes. These findings offer actionable insights for management to facilitate smoother transitions and foster a supportive environment for employees. This research provides a unique contribution by shedding light on M&A dynamics in the context of Nepalese banks and offering practical recommendations for enhancing employee performance through strategic management practices.